Tumor microenvironment responsive metal nanoparticles in cancer immunotherapy - Yang, Rou; Chen, Lu; Wang, Yiling; Zhang, Lijuan; Zheng, Xi; Yang, Yong; Zhu, Yuxuan (Frontiers in Immunology, 2023)
Malignant tumors have a unique tumor microenvironment (TME), which includes mild acidity, hypoxia, overexpressed reactive oxygen species (ROS), and high glutathione (GSH) levels, among others. Recently, TME regulation approaches have attracted widespread attention in cancer immunotherapy. Nanoparticles as drug delivery systems have ability to modulate the hydrophilicity of drugs to affect drug uptake and efflux in tumor. Especially, the metal nanoparticles have been extensive applied for tumor immunotherapy due to their unique physical properties and elaborate design. However, the potential deficiencies of metal nanoparticles due to their low biodegradability, toxicity and treatment side effects restrict their clinical application. In this review, we briefly introduce the feature characteristics of the TME and the recent advances in tumor microenvironment responsive metal nanoparticles for tumor immunotherapy. In addition, nanoparticles could be combined with other treatments, such as chemotherapy, radiotherapy and photodynamic therapy also is presented. Finally, the challenges and outlook for improving the antitumor immunotherapy efficiency, side effect and potential risks of metal nanoparticles has been discussed.